Biological Control with Insects: The Waterhyacinth Weevils - Ted D. Center; F. Allen Dray; Vernon V. Vandiver; Lyn A. Gettys; Philip W. Tipping (EDIS)
This 2-page fact sheet is a minor revision written by Ted D. Center, F. Allen Dray, Vernon V. Vandiver Jr., Lyn A. Gettys, and Philip W. Tipping, and published by the Agronomy Department, April 2017.